Dictyosteliumdiscoideum–Mycobacterium marinum infection model: a powerful high-throughput screening platform for anti-infective compounds - Nitschke, Jahn; Hanna, Nabil; Soldati, Thierry (Frontiers in Microbiology, 2025)
Tuberculosis is among the world’s deadliest diseases, causing approximately 2 million deaths annually. The urgent need for new antitubercular drugs has been intensified by the rise of drug-resistant strains. Despite recent advancements, most hits identified through traditional target-based screening approaches exhibit limited efficacy in vivo. Consequently, there is a growing demand for whole-cell-based approaches that utilize host-pathogen systems directly. The Dictyostelium discoideum–Mycobacterium marinum host–pathogen system is a well-established and powerful alternative model system for studying mycobacterial infections. In this article, we present a phenotypic host–pathogen assay protocol that monitors M. marinum during infection of the amoeba D. discoideum. This assay is characterized by its scalability for high-throughput screening, robustness, and ease of manipulation, making it an effective system for compound screening. Notably, this system provides dual readouts: bacterial load via a bioluminescent M. marinum strain and host survival and growth via a fluorescent D. discoideum strain, enabling further host characterization by quantifying growth inhibition and potential cytotoxicity. Finally, the assay was benchmarked against selected antibiotics and anti-infectives, and IC50s and MIC values were calculated where applicable, demonstrating its ability to differentiate between antibiotics and anti-infective compounds.